2018
DOI: 10.33582/2639-9237/1002
|View full text |Cite
|
Sign up to set email alerts
|

Wunderlich’s syndrome in a young man of testicular mixed germ cell tumor with choriocarcinoma syndrome

Abstract: s syndrome in a young man of testicular mixed germ cell tumor with choriocarcinoma syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Within the group of germ cell tumors, pure choriocarcinoma is found in 0.3%–1% of these neoplasms and mixed form in 8%, 1 this type of tumor has an aggressive oncological behavior with high metastatic capacity such as choriocarcinoma syndrome which causes bleeding in metastatic sites and significant morbidity and mortality 3 ; Alvarado/Hernandez et al reported a series of 15 patients with choriocarcinoma as a pure or predominant component, finding 100% of cases with metastases (pulmonary 66%, hepatic 60%, brain 20% gastrointestinal tract 13% and renal 6%) 4 ; There are few studies or reports in the literature of retroperitoneal bleeding or better known as Wunderlich syndrome in association with testicular cancer, finding publications such as Yee-Huang Ku et al, in 2018 reporting a case of spontaneous retroperitoneal bleeding secondary to testicular choriocarcinoma, 3 or as published in 1992 by Huang et al reporting another case of choriocarcinoma-type testicular carcinoma with metastatic retroperitoneal involvement associated with Wunderlich syndrome 5 ; In our case, the high aggressiveness of this type of testicular tumors is clearly evidenced, documenting metastasis to the kidney and mesentery, confirming with the histopathological result the commitment to choriocarcinoma, which is of very little presentation in the world literature, therefore, an early onset of chemotherapy is required in order to reduce this rate of metastasis and high morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Within the group of germ cell tumors, pure choriocarcinoma is found in 0.3%–1% of these neoplasms and mixed form in 8%, 1 this type of tumor has an aggressive oncological behavior with high metastatic capacity such as choriocarcinoma syndrome which causes bleeding in metastatic sites and significant morbidity and mortality 3 ; Alvarado/Hernandez et al reported a series of 15 patients with choriocarcinoma as a pure or predominant component, finding 100% of cases with metastases (pulmonary 66%, hepatic 60%, brain 20% gastrointestinal tract 13% and renal 6%) 4 ; There are few studies or reports in the literature of retroperitoneal bleeding or better known as Wunderlich syndrome in association with testicular cancer, finding publications such as Yee-Huang Ku et al, in 2018 reporting a case of spontaneous retroperitoneal bleeding secondary to testicular choriocarcinoma, 3 or as published in 1992 by Huang et al reporting another case of choriocarcinoma-type testicular carcinoma with metastatic retroperitoneal involvement associated with Wunderlich syndrome 5 ; In our case, the high aggressiveness of this type of testicular tumors is clearly evidenced, documenting metastasis to the kidney and mesentery, confirming with the histopathological result the commitment to choriocarcinoma, which is of very little presentation in the world literature, therefore, an early onset of chemotherapy is required in order to reduce this rate of metastasis and high morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%